2021
DOI: 10.1371/journal.pone.0245130
|View full text |Cite
|
Sign up to set email alerts
|

Online pragmatic interpretations of scalar adjectives are affected by perceived speaker reliability

Abstract: Linguistic communication requires understanding of words in relation to their context. Among various aspects of context, one that has received relatively little attention until recently is the speakers themselves. We asked whether comprehenders’ online language comprehension is affected by the perceived reliability with which a speaker formulates pragmatically well-formed utterances. In two eye-tracking experiments, we conceptually replicated and extended a seminal work by Grodner and Sedivy (2011). A between-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…First, to determine if speaker reliability could be detected from the speaker's language use itself; and second, to make the experiment more ecologically valid. The latter stems from the observation that overt signaling of speaker unreliability is typically unavailable in real-life contexts (Gardner et al 2021).…”
Section: Methodsmentioning
confidence: 99%
“…First, to determine if speaker reliability could be detected from the speaker's language use itself; and second, to make the experiment more ecologically valid. The latter stems from the observation that overt signaling of speaker unreliability is typically unavailable in real-life contexts (Gardner et al 2021).…”
Section: Methodsmentioning
confidence: 99%
“…More specifically, speaker identity (also known as speaker- or talker-specificity) has been shown to be an influential factor in language processing across multiple linguistic domains, such as phonology (Roettger & Franke, 2019 ; Trude & Brown-Schmidt, 2012 ), spoken word recognition (Arnold et al, 2007 ; Creel et al, 2008 ), sentence processing (Kamide, 2012 ), and semantics/pragmatics (Bergen & Grodner, 2012 ; Gardner et al, 2021 ; Pogue et al, 2016 ; Yildirim et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Research on a range of linguistic-pragmatic phenomena has demonstrated speaker-specific effects on the interpretation of pragmatic intent. For example, contrastive inferences are suspended if a particular speaker habitually overmodifies a noun, e.g., ‘the tall cup’ when referring to a singleton item (Gardner et al, 2021 ; Grodner & Sedivy, 2011 ), and listeners infer that previously under-informative speakers will remain so in their descriptions using different adjectives (Pogue et al, 2016 ). Similarly, addressees adapt to speaker-specific tendencies in the intended meaning of scalar quantifiers such as ‘some’ and ‘many’ (Yildirim et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…If, however, contrastive inferences are more automatized or context‐invariant, the behavior of a situation‐specific speaker may have no or little influence on listeners' interpretation. Using these paradigms, studies have shown that, under certain circumstances, adult listeners adjust their contrastive inferences when given evidence that highlights the non‐conventional communicative behavior of the speaker (Gardner et al, 2021; Grodner & Sedivy, 2011; Ryskin et al, 2019). However, to produce this effect, it appears that the relevant evidence needs to be both exceptionally strong and abundant, including the speaker's use of over‐ and under‐informative descriptions, incorrect labels, and often explicit statements about the speaker's language impairment (Grodner & Sedivy, 2011; Ryskin et al, 2019).…”
mentioning
confidence: 99%
“…The manipulation varying speaker conventionality was somewhat different than past studies. In previous research, the unconventional speaker produced various types of non‐optimal sentences: over‐informative descriptions (i.e., where adjectives were unnecessary), under‐informative descriptions (i.e., where the lack of modifiers led to referential ambiguity), and sometimes incorrect descriptions (i.e., where the labeling of object or location was wrong; Gardner et al, 2021; Grodner & Sedivy, 2011; Ryskin et al, 2019). Under‐informative and incorrect descriptions provided by a speaker might give children the impression that the speaker is unreliable and inaccurate instead of unconventional in language use.…”
mentioning
confidence: 99%